“Evaluación de la implementación de cuatro niveles de harina de residuos de cascarilla de cacao (theobroma cacao l) como sustituto del maíz, en la alimentación de pollos de engorde” - Lara Ramirez, Shyrley Rocio (2023)
In the current research, it was assessed the cocoa husk residue flour four levels implementation, as a corn substitute in broiler chicken feed. The proposed aims were: the cocoa husk residue flour bromatological, microbiological and physical characterization, for verifying its composition and properties, and subsequently, it was replaced in the feeding diets. Also, it was assessed the productive parameters (Weight, feed consumption, weight gain, feed conversion, mortality, yield to the carcass), as well as, the cost/benefit indicator, when replacing said flour. The study was made in the Quito city for a 7 weeks period, which it was used a completely randomized design, with 100 bb male chickens from Ross 308 line, the randomly distributed into 5 treatments, made up 20 birds, each one and 4 repetitions. For the data analysis was used variance (ANOVA) analysis and the Bonferroni Test. Regarding the bromatological, microbiological and physical analysis, they were got positive results at a 15.07 % protein percentage, evidencing the pathogenic agents absence and a 147.3 µm acceptable particle size. The research did not show significant differences for average weight to end at the experimental phase, presenting higher values for T1 (2%) with a 3212.5g weight, and the lowest weight for T2 (4%) with a 2850g weigh, however, the weight gain revealed statistical differences in the last week the study, presenting higher values for T4 (8%) of 1300g unlike, what reported for T1 (2%) with 1112.50g, which demonstrates a broiler chicken fed weight increase with a diet, which was 8% maize by cocoa husk residue meal, their seventh week of life. The research results expose positive effects for the T1 (2%), along the experimental phase, further, it got the best cost benefit index for this treatment, since there was a 0.50 cents profit, for every $1, therefore, the corn partial substitution by the cocoa husk residue flour, at 2%, as a protein source in the broiler chickens diet.